Using a mixture of cottonseed hulls and cottonseed meal to replace alfalfa hay in diets for stressed feeder calves - Farran, T.B.; Hunter, R.D.; Montgomery, Sean P.; Sindt, J.J.; Blasi, Dale A.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One 28-day receiving experiment was conducted using 625 exotic × British cross heifers to evaluate growth performance and morbidity on receiving diets that contained either alfalfa hay or a pellet composed of 65% cottonseed hulls and 35% cottonseed meal as the roughage source. Heifers fed the cotton byproduct pellet consumed more feed (P<0.01) but tended to be less efficient than those fed alfalfa hay. Daily gain was comparable between diets (P>0.05), and the percentages of heifers diagnosed, treated, or retreated for respiratory disease were similar.
Keywords: Beef; Cottonseed hulls; Receiving cattle; Health